2021
DOI: 10.1177/1468087420986751
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transient needle lift on the internal flow and near-nozzle spray characteristics for modern GDI systems investigated by high-speed X-ray imaging

Abstract: The development of the injector nozzle is a dynamic area in regard of several technical aspects. At first, the internal flow influences the near-field spray characteristics via various phenomena such as cavitation and turbulence. However, these phenomena are not fully understood due to their extremely fast, complex and multiscale nature. Furthermore, it governs the spray targeting inside the combustion chamber. High-speed X-ray imaging of GDI injector nozzles is performed in this study. The experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Although the transient effect is over a short period of time, it has a great impact on internal flow structure, especially at high injection pressures with diesel injectors, which influences the near field emerging spray and then atomization and combustion. The subject has been investigated previously and the most recent experimental work 28 used X-ray imaging and showed the transient behavior of liquid jet at the nozzle exit. Also, Strotos et al 29 simulated the transient heating effects in high-pressure diesel injector and showed that increasing the injection pressure from 2000 to 3000 bar, caused a considerable increase in fluid temperature to above the boiling point and thus leading to fuel boiling and instability.…”
Section: Introductionmentioning
confidence: 99%
“…Although the transient effect is over a short period of time, it has a great impact on internal flow structure, especially at high injection pressures with diesel injectors, which influences the near field emerging spray and then atomization and combustion. The subject has been investigated previously and the most recent experimental work 28 used X-ray imaging and showed the transient behavior of liquid jet at the nozzle exit. Also, Strotos et al 29 simulated the transient heating effects in high-pressure diesel injector and showed that increasing the injection pressure from 2000 to 3000 bar, caused a considerable increase in fluid temperature to above the boiling point and thus leading to fuel boiling and instability.…”
Section: Introductionmentioning
confidence: 99%
“…The upgrade from previous Bosch GDI injectors resulted in higher fuel injection dosing accuracy, improved fuel atomization and reduced jet penetration, reduction in nozzle wetting due to improved bore geometry. This resulted into a substantial decrease in exhaust emissions, especially in the particle number (Pauer et al 2017;Hartmann et al 2018;Hassdenteufel et al 2022;Mamaikin et al 2022). An enlarged view of the injector tip is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In any case, the high penetrating power of x-rays allows otherwise inaccessible areas of the spray to be quantitatively characterized, such as in the near-field region immediately at the injector exit and even inside the nozzle. This proves invaluable, for example, when studying the primary atomization phase of sprays (Tekawade et al 2020;Arienti et al 2021;Mamaikin et al 2022). However, to the detriment of its diagnostic potential, objective experimental constraints restrict the range of operating conditions that can be explored through x-ray absorption methods.…”
Section: Introductionmentioning
confidence: 99%
“…9 Needle lift at the top of the needle has been measured by laser Doppler vibrometry, 10 and lift and wobble (radial motion) of the check ball have been observed via optically transparent nozzles 11,12 and x-ray imaging. [13][14][15] However, it is not possible to make an entire injector optically transparent due to the high fuel pressure, and the thick metal cross section of the solenoid makes x-ray imaging challenging. A full accounting of the internal dynamics of injectors has not yet been achieved.…”
Section: Introductionmentioning
confidence: 99%